Evaluation of safety health and environment at selected area: Construction site / Ahmad Azwan Anuar - Ahmad Azwan, Anuar (2022)
Due to the complexity and unpredictability of the operations, the construction industry has a high prevalence of serious and fatal occupational injuries. Efforts to reduce workplace accidents through various safety improvement methods have reached a roadblock after decades of effort. Department of Occupational Safety and Health (DOSH) reports that the construction industry's safety has improved, but a closer examination indicates that it still lags below most other industries. Statistics also shows a decrease in the number of the recorded cases since 2019 but it was only because most construction projects were put on hold due to COVID-19. Accidents in construction site impacts the project performance, including delays in project completion, increases in project costs, decreased productivity, and poor perceptions of the company. Accidents result from a combination of contributing causes and in order to improve the overall safety performance, it is necessary to investigate the root causes. This study examined reported accident cases kept by DOSH and carried out questionnaires survey to the construction team to collect data. The finding of this study identified the category of the factors; unsafe method, human element, unsafe equipment, job site conditions, management and unique nature of the industry. The results concluded that the main cause of construction accidents are worker’s attitude, negligence, poor site management, failure to use PPE and working at high level.